KAJIAN ETNOMATEMATIKA: EKSPLORASI KOMPLEKS MAKAM RAJA-RAJA IMOGIRI SEBAGAI BAHAN PEMBELAJARAN MATEMATIKA - Dita Aldila Krisma; Arifta Nurjanah (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
Ethnomatematics-based learning, linking mathematics and culture, can improve students' mathematical abilities. Therefore, the mathematical concepts contained in culture need to be studied to become one of the innovations in learning mathematics as a contextual learning material. This research aimed to explore and describe the cemetery complex of the Imogiri kings. This research was exploratory-qualitative research with an ethnographic design. The focus of this research was the ethnomathematics exploration of the buildings in the cemetery complex of the Imogiri kings. Research data collection was carried out through observation and documentation. The findings show that in the cemetery complex of the Imogiri kings, there are mathematical concepts that can be used as materials for learning mathematics. The mathematical concepts contained in the complex can be related to operational material for the addition of integers, comparisons, trapezoids, rectangles, congruence, similarity, beams, truncated pyramids, reflections, and rotations. The mathematical concepts from the ethnomathematics study can be used as materials for learning mathematics in schools, including at the elementary and junior high school levels.